Contributions of Printed Material in the Teaching of English as a Foreign Language During the Period of Distance Education in the Municipality of Saboyá - Guerrero Beltran, Juan Manuel; Flórez Delgado, Yenny Paola; Pérez Jimenez, Maria Fernanda; Perez Pereira, Nicole Marie (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This project focuses on a qualitative research method called intrinsic case study, which aims to explore and analyze the contributions of printed material in the teaching of English as a foreign language in four public and elementary schools in rural and urban areas of Saboyá, Boyacá. The project arose due to the changes that occurred in distance learning from June to November 2020. The instruments used to collect information were a survey, a structured interview, and the printed material designed by the teachers. The results of the research showed the decision-making process that the teachers carried out when preparing their classes, in which they included topics from other subjects. This methodology is known as Content and Language Integrated Learning (CLIL).  In addition, the design of the printed material was suitable to achieve the objectives of the class and helped the students to improve their fine motor skills and English vocabulary